Sistem Pengupahan di CV. Be Clean Makassar berdasarkan Perspektif Maslahah (AT TAWAZUN: Jurnal Ekonomi Islam, 2022)
Conflict between workers and employers has become a phenomenon. A number of demands that arise in every demonstration, the gap between the welfare of workers with the cost of living and the work done in the workplace. This study aims to determine the wage system in CV. Be Clean Makassar with a perspective review of maslahah. This study uses a phenomenological research with a qualitative approach. The sample in this study were workers and business owners CV. Be Clean Makassar. This study uses data collection methods using interviews, observation and documentation. The results of this study are assessed from the fact that maslahah must be in line with the objectives of the Shari'a, maslahah must be generally accepted, maslahah must be true, not conjecture. Wage system in CV. Be Clean Makassar shows that its wage system is in line with the shari'a objective of providing wages at the beginning of the month, never delaying payment of wages. However, the wage system at CV Be Clean Makassar has not been able to provide wages based on the Gowa UMP.